ALUMINIUM(III), Fe(II) COMPLEXES AND DYEING PROPERTIES OF APIGENIN (5,7,4 '-TRIHYDROXY FLAVONE) - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2010)
Apigenin and its metal complexes are used extensively in chemistry, biology and the dye industry. In this study, the interactions of flavonoids with metal ions and dyeing properties of these complexes are studied and these complexes of apigenin with aluminium and iron are examined by spectrophotometric and potentiometric methods. The stability constants of these complexes were determined potentiometrically. The evaluated protonation constants of the apigenin were found: logK(1) = 8.21 and logK(2) = 2.83 at the 25 degrees C. Logarithms of the stability constants were found: for aluminium complex: logK(1) = 8.24, logK(2) = 7.46, and logK(3) = 7.04 and for iron complex: logK(1) = 7.52, logK(2) = 5.80, and logK(3) = 5.00 at the 25 degrees C. The components of metal-apigenin complexes are given: 1:3 (metal: apigenin ratio) both Al(III) and Fe(II) from the results. According to our work; it can be said that Al(III) apigenin and Fe(II) apigenin complexes are formed in the dyeing process and this increases the lightfastness of the dyeing.
Keywords: apigenin; iron; aluminium; stability constant; potentiometry; spectrophotometry; dyeing; QUERCETIN 3,3',4',5,7-PENTAHYDROXYFLAVONE COMPLEXES; STABILITY-CONSTANTS; SPECTROPHOTOMETRIC DETERMINATION; ANTIOXIDANT ACTIVITY; IRON(II)